THE FACTORS OF STUDENTS’ SILENCE IN THE ENGLISH SPEAKING CLASSROOM PERFORMANCE AT ELEVENTH GRADE OF SMKN 1 TEMBILAHAN - Anjas Pratama; Sri Erma Purwanti; Melda Yeni (J-Shelves of Indragiri (JSI), 2021)
The phenomenon of silent students often occurs in the learning process of English, especially in English speaking classes, where students do not respond to the teacher when the learning process is running, so this interferes with the smooth learning process. This study aims to determine the factors that cause students to be silent when learning in English speaking class and determine the dominant factor in the eleventh grade of SMKN 1 Tembilahan. This research is a quantitative descriptive study. This research instrument uses a questionnaire that contains 20 statements. Moreover, the total population is 459 students, and the total samples taken 25% of the total population, as many as 116 students. The sampling technique in this study was random sampling. The sample used in this study was the 11th-grade students of all departments in the SMKN 1 Tembilahan school. Based on calculating students' responses to 20 questionnaire statements, it was found that ten factors caused students to be silent when learning English. They are inadequate vocabulary, the inability to manage vocabulary, lack of understanding of English grammar, unconfident in their abilities, afraid of making mistakes, lack of pronunciation, feeling nervous while speaking, getting difficulty in understanding English material, afraid of being criticized, and feeling embarrassed to speak in front of the class. While the dominant factor comes from the indicator (students' proficiency), which has 4 points, the first point is that grammar understanding is still lacking, then the second point is a lack of self-confidence, and for the third and fourth points, they have the same point which is about vocabulary. Based on the results of the study, it can be concluded that the ten statements above are the factors that cause students to stay silent in learning English and the dominant. They come from the indicators (students' proficiency) in the eleventh grade of SMKN 1 Tembilahan, as the researcher explained above.